Bullying in the Perspective of the Quran - Rofiqoh, Nihayatur; Abitolkha, Amir Maliki (research, training and philanthropy institution Natural Aceh, 2025)
This research is motivated by Muslims who lack ethics and misbehave, such as in cases of Bullying, which are still underestimated by the general public. This is very contrary to Islamic teachings. This research uses descriptive qualitative research analysis, namely an effort to collect data, first compiled, explained, and then analyzed. This type of research is library research, which makes library material the primary data source in this study. The data collection technique in the research is searching and observing the verses of the Qur'an related to Bullying and the interpretations related to the verse. Then, review books, journals, articles, and previous theses/theses that match the theme to be studied. Then, all the data obtained will be collected and analyzed using the maudu'i interpretation method. The result of this study is that Bullying is a form of injustice, which is a real enemy of Islam. Islamic teachings emphasize the importance of compassion and doing good and prohibit actions that denounce, rebuke, or demean others. As creatures of Allah SWT, we should help each other in goodness and not demean or put down each other. Islam emphasizes the values of tolerance, cooperation, and mutual respect for all humans, without exception, who must be treated with respect and respect and respect each other.